2007
DOI: 10.1631/jzus.2007.b0331
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the efficacy of influenza vaccination (H5N1) in chicken by using extract of Cochinchina momordica seed (ECMS)

Abstract: Seeds of a Chinese traditional medicine plant, Cochinchina momordica were used in the present study for the improvement of influenza vaccine (H5N1) in chicken. Crude extraction from Cochinchina momordica seed (ECMS) was obtained by ethanol extraction method. In experiment No. 1, two weeks old chickens were immunized with influenza vaccine (H5N1) alone or combined with ECMS (5, 10, 20, 40 and 80 microg/dose). Serum IgG antibody levels (by ELISA) as well as effects on daily weight gain were measured on 0, 7, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionsupporting
confidence: 72%
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, ECMS has been found effective in stimulation of the immune response to vaccination against H5N1 avian influenza in chickens (24). In this study, we demonstrated that ECMS and oil emulsion synergistically promoted the production of IgG1 and IgG2 elicited by FMDV antigens in a guinea pig model, as shown in Fig.…”
Section: Discussionsupporting
confidence: 62%
“…(ECMS), has an adjuvant effect on the immune responses elicited by ovalbumin (OVA), with a much lower hemolytic activity (30). ECMS has also been proven effective in enhancing immune responses to vaccination against avian influenza (H5N1) in chickens (24). The medical use of the seeds has been described in ancient Chinese medical literature, Kai Bao Materia Medica, from the Song Dynasty (AD 793) (10) and is currently included in both Chinese pharmacopoeia (5) and Chinese veterinary pharmacopoeia (6).…”
mentioning
confidence: 99%
“…Many viruses are threatening the health and welfare of poultry and have even struck the poultry industry and brought tremendous economic losses to the world, such as the case of the highly pathogenic avian influenza (HPAI) in recent years. At present, vaccina- tion is the great asset for outbreak containment of avian disease (Habib et al, 2006;Rajput et al, 2007). However, the intensive use of vaccines is driving virus to increase its virulence such as the case of the MDV with greater virulence in vaccinated chickens (Witter, 1997).…”
Section: Introductionmentioning
confidence: 99%